2020
DOI: 10.1186/s12885-020-07200-w
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of spread through air spaces in lung adenocarcinoma and squamous cell carcinoma using the 8th edition AJCC/UICC staging system

Abstract: Background: This study aimed to comprehensively investigate the effect of spread through air spaces (STAS) on clinicopathologic features, molecular characteristics, immunohistochemical expression, and prognosis in lung adenocarcinomas (ADC) and squamous cell carcinomas (SQCC) based on the 8th edition AJCC/UICC staging system. Methods: In total, 303 ADC and 121 SQCC cases were assessed retrospectively. Immunohistochemical staining was performed for E-cadherin, vimentin, Ki67, survivin, Bcl-2, and Bim. Correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…A total of 1047 articles were searched:9 from CBM, 158 from Embase, 251 from PubMed, 194 from Web of science,130 from Wanfang date, 32 from Veep and 273 from CNKI. After carefully inspection of these articles, 12 Original studies 7,[11][12][13][14][15][16][17][18][19][20][21] were nally enrolled in our meta-analysis. The detail processes of study selection were showed in the ow diagram (Fig.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 1047 articles were searched:9 from CBM, 158 from Embase, 251 from PubMed, 194 from Web of science,130 from Wanfang date, 32 from Veep and 273 from CNKI. After carefully inspection of these articles, 12 Original studies 7,[11][12][13][14][15][16][17][18][19][20][21] were nally enrolled in our meta-analysis. The detail processes of study selection were showed in the ow diagram (Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…A total of 11 original studies were included [11][12][13][14][15][16][17][18][19][20][21] . We combined these studies using random effects.…”
Section: Results Of Meta-analysis 221 the Association Between Egfr Genotype And Stas In Lung Adenocarcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, no significant difference was observed in the downregulation of E-cadherin, another EMT marker. However, Jia et al 27 reported that STAS was associated with low-E-cadherin expression, and high vimentin expression in adenocarcinoma and squamous cell carcinoma. Furthermore, Jin et al 52 reported that c-ros oncogene 1 (ROS1)-rearranged lung cancer showed frequent STAS-like aerogenous spread manifested by a decrease in Ecadherin levels; Lee et al 16 also reported that ROS-1 was highly expressed at 71% of STAS-positive tumors.…”
Section: Association With Molecular Propertiesmentioning
confidence: 99%